Mutation Breeding in Coffee with Special Reference to Leaf Rust Protocols - Ingelbrecht, Ivan L.W; Silva, Maria do Céu Lavado da; Jankowicz-Cieslak, Joanna (Springer Berlin Heidelberg : Imprint: Springer, 2023)
This open-access book presents essential concepts and new, illustrated methods for mutation-assisted breeding of Coffea arabica L. (Arabica), one of the world's most important cash crops and beverages. Arabica coffee accounts for about 60% of the world's coffee production. Coffee leaf rust (CLR), caused by the fungus Hemileia vastatrix is the major disease affecting Arabica coffee resulting in losses of over $1 billion annually. The geographical distribution of CLR is expanding due to climate change. Moreover, the genetic improvement of Arabica coffee is constrained due to its very narrow genetic base. This protocol book covers practical methods to enhance genetic diversity in Arabica coffee through induced mutagenesis and for screening for resistance to CLR. Current breeding approaches, challenges, and opportunities for Arabica coffee improvement are briefly reviewed and a survey of common coffee diseases with emphasis on CLR is presented. Based on latest advances inscience and technology, this book includes novel methods for single-cell mutagenesis using in vitro cell and tissue culture techniques and for genome-wide screening of induced mutations using genomics tools. Each protocol chapter provides step-by-step illustrated methods supported by example results. Given the impact of recent CLR epidemics on Arabica coffee production in Latin America, the book is intended to serve as a timely reference and guide for students and researchers in the agricultural sciences, plant pathologists and breeders, as well as growers and end-users interested in producing novel coffee genotypes for genetic studies, breeding, and commercial applications. .